An Ordinance respecting marriages [electronic resource]. - Northwest Territories. An Ordinance Respecting Marriages. ([Battleford, N.W.T.? : s.n., 1878)
Printed ephemera. Caption title. At head of title: North-West Territories, No. 9 of 1878. Electronic reproduction. Mode of access: Internet. 44